2017
DOI: 10.5194/acp-17-5107-2017
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistency of ammonium–sulfate aerosol ratios with thermodynamic models in the eastern US: a possible role of organic aerosol

Abstract: Abstract. Thermodynamic models predict that sulfate aerosol (S(VI) ≡ H 2 SO 4 (aq) + HSO − 4 + SO 2− 4 ) should take up available ammonia (NH 3 ) quantitatively as ammonium (NH + 4 ) until the ammonium sulfate stoichiometry (NH 4 ) 2 SO 4 is close to being reached. This uptake of ammonia has important implications for aerosol mass, hygroscopicity, and acidity. When ammonia is in excess, the ammonium-sulfate aerosol ratio R = [NHshould approach 2, with excess ammonia remaining in the gas phase. When ammonia is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
111
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 60 publications
4
111
1
Order By: Relevance
“…The hypothesis of organic films, however, is in stark contrast to established literature showing that NH3, water vapor, and HNO3 equilibrate with organic-rich 30 aerosols (Fountoukis et al, 2009;Guo et al, 2015;Guo et al, 2016;Guo et al, 2017a). Such a film, as proposed by Silvern et al (2017), selectively limits NH3, but not H2O and HNO3 molecules that are both larger than NH3 hence more difficult to diffuse through media. At low temperature or low relative humidity, aerosols may be in semi-liquid or glassy state and have very low diffusivity of molecules throughout its volume (Tong et al, 2011;Bones et al, 2012).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…The hypothesis of organic films, however, is in stark contrast to established literature showing that NH3, water vapor, and HNO3 equilibrate with organic-rich 30 aerosols (Fountoukis et al, 2009;Guo et al, 2015;Guo et al, 2016;Guo et al, 2017a). Such a film, as proposed by Silvern et al (2017), selectively limits NH3, but not H2O and HNO3 molecules that are both larger than NH3 hence more difficult to diffuse through media. At low temperature or low relative humidity, aerosols may be in semi-liquid or glassy state and have very low diffusivity of molecules throughout its volume (Tong et al, 2011;Bones et al, 2012).…”
Section: Introductionmentioning
confidence: 78%
“…This method reports the pH for a HSO4 -/SO4 2-aerosol system similar to the fine particle pH predicted by a thermodynamic modeling used in this study (Guo et al, 2015)) has led to the use of measurable aerosol properties as acidity proxies, such as aerosol ammoniumsulfate ratio or ion balances (e.g. (Paulot and Jacob, 2014;Wang et al, 2016;Silvern et al, 2017)). Recent work has shown that 10 acidity proxies are not uniquely related to pH, which in turn strongly questions any conclusions derived from its use.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations